Pathways to the Brain: Impact of Fine Particulate Matter Components on the Central Nervous System - Yasuhiro Ishihara; Miki Tanaka; Naoyuki Nezu; Nami Ishihara; Ami Oguro; Christoph F. A. Vogel (Antioxidants)
Fine particulate matter with an aerodynamic diameter ≤ 2.5 µm (PM2.5) has been extensively studied due to its adverse health effects. Most research has focused on its impact on the respiratory system; however, increasing attention is being directed toward its effects on the brain. Associations between air pollution and neurological disorders—such as Alzheimer’s disease, cerebral infarction, and autism spectrum disorder—have been reported, with mechanism-based studies in animal models providing further insights. PM2.5 comprises a complex mixture of thousands of chemical constituents. To elucidate its neurotoxicity mechanisms, it is essential to investigate both its transport pathways to the brain and the specific actions of its individual components. This review highlights key PM2.5 components—water-soluble ions, metals, carbonaceous particles, polycyclic aromatic hydrocarbons, quinones, plastics, and bioaerosols—and outlines their potential routes of entry into the central nervous system, along with their associated mechanisms of action. By integrating these findings, this review contributes to a deeper understanding of the neurological effects mediated by PM2.5, which represent one of the most critical aspects of its health impact.